2021
DOI: 10.3389/fimmu.2021.649572
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 and IRF8 Modulate Activation of NLRP3 Inflammasome via Regulating Its Expression in Human Macrophages

Abstract: NLRP3 inflammasomes play crucial roles in the initiation of host defense by converting pro-Caspase-1 to mature Caspase-1, which in turn processes immature IL-1β and IL-18 into their biologically active forms. Although NLRP3 expression is restricted to monocytic lineages such as monocytes, macrophages, and dendritic cells, the mechanisms determining the lineage-specific expression of NLRP3 remain largely unknown. In this study, we investigated the transcription factors involved in cell-type-specific transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…IL-1 β and IL-18 have been shown to be essential for optimal activation of the antifungal activity of macrophages [ 15 ]. Polymorphisms in the IL-1 gene cluster may be important for susceptibility or resistance to invasive pulmonary aspergillosis in humans.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1 β and IL-18 have been shown to be essential for optimal activation of the antifungal activity of macrophages [ 15 ]. Polymorphisms in the IL-1 gene cluster may be important for susceptibility or resistance to invasive pulmonary aspergillosis in humans.…”
Section: Introductionmentioning
confidence: 99%
“…THP-1 cells were used to study the secretion of the inflammasome by inflammatory cells in acne lesions. Since it is well documented that cultured THP-1 has the molecular constitution required for inflammasome assembly [ 29 ], we sought to confirm whether P. acnes stimulates the secretion of IL-1β in vitro. After cells were treated with active P. acnes , IL-1β expression in the cytoplasm was up-regulated at the transcription level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PU.1 is also involved in macrophage-involved inflammation, studies have shown, PU. 1 activates macrophages and increases the inflammatory response by regulating NLRP3 inflammasome [ 41 ]. Interestingly, PU.1 may serve as an important target for vitamin D3 to alleviate atopic dermatitis, a severe inflammatory skin disease [ 42 ].…”
Section: Discussionmentioning
confidence: 99%